1º Encontro de Arqueologia do Algarve - Rocha, Leonor (2010)
The archaeological intervention described in this communication has revealed the existence of an isolated grave, apparently from the late roman period, located at Perna Seca, Municipality of Silves, and was done as an emergency operation, in a joint effort between the Portuguese Institute of Archaeology and the Silves Municipal Council.